2007
DOI: 10.1158/0008-5472.can-06-3607
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Targeted Enzyme/Prodrug Therapy Mediates Long-term Disease-Free Survival of Mice Bearing Disseminated Neuroblastoma

Abstract: Neural stem cells and progenitor cells migrate selectively to tumor loci in vivo. We exploited the tumor-tropic properties of HB1.F3.C1 cells, an immortalized cell line derived from human fetal telencephalon, to deliver the cDNA encoding a secreted form of rabbit carboxylesterase (rCE) to disseminated neuroblastoma tumors in mice. This enzyme activates the prodrug CPT-11 more efficiently than do human enzymes. Mice bearing multiple tumors were treated with rCE-expressing HB1.F3.C1 cells and schedules of admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 14 publications
4
114
1
Order By: Relevance
“…8,11,12 We have previously demonstrated that F3 human NSCs expressing the cytosine deaminase prodrug gene are endowed with selective migratory capacity and therapeutic effects against brain metastases from breast cancer. 11 Similarly, we reported that F3 NSCs transduced with the cytosine deaminase gene exhibit tropism and bystander killing effects for leptomeningeal medulloblastomas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8,11,12 We have previously demonstrated that F3 human NSCs expressing the cytosine deaminase prodrug gene are endowed with selective migratory capacity and therapeutic effects against brain metastases from breast cancer. 11 Similarly, we reported that F3 NSCs transduced with the cytosine deaminase gene exhibit tropism and bystander killing effects for leptomeningeal medulloblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] HB1.F3.rCE (F3.rCE) cells were prepared by transduction with replication-deficient retrovirus that harbor the pLPCX vector, which contains the rCE gene. 12 Vectors were packaged by co-transduction of the rCE puromycin plasmid with the MV12 envelope-coding plasmid cDNA into pA317 cells. The retroviral supernatant was used for multiple infections of F3 cells.…”
Section: Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thanks to their non imunogenic character, allogeneic MSCs can substitute for autologous stem cells. We and others (Danks et al, 2007;Nakamura et al, 2004;Nakamizo et al, 2005) are encouraged by the results of stem cell driven enzyme prodrug therapy experiments to treat glioblastoma multiforme, a tumor with fatal prognosis. Our experiments took the advantage of the fact that human AT-MSCs are not immunogenic in treatment of rat glioblastoma C6 growing intracebroventriculary.…”
Section: Stem Cell Based Gene Therapymentioning
confidence: 99%